2003
DOI: 10.1046/j.1365-313x.2003.01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Lhcb1 and Lhcb2 proteins of the light‐harvesting complex of photosystem II – effects on photosynthesis, grana stacking and fitness

Abstract: SummaryWe have constructed Arabidopsis thaliana plants that are virtually devoid of the major light-harvesting complex, LHC II. This was accomplished by introducing the Lhcb2.1 coding region in the antisense orientation into the genome by Agrobacterium-mediated transformation. Lhcb1 and Lhcb2 were absent, while Lhcb3, a protein present in LHC II associated with photosystem (PS) II, was retained. Plants had a pale green appearance and showed reduced chlorophyll content and an elevated chlorophyll a/b ratio. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(56 citation statements)
references
References 43 publications
5
51
0
Order By: Relevance
“…Consistently, previous studies showed that down-regulation of the LHCB members reduced plant tolerance to environmental stresses with lowered seed production (Andersson et al , 2001, 2003; Ganeteg et al , 2004; Kovacs et al , 2006) except for the lhcb3 mutant that showed comparable seed production with that of wild-type plants (Damkjaer et al , 2009). The differences observed in the lhcb3 mutants between our present observations and the previously reported data (Damkjaer et al , 2009) may be due to the characteristics of the different lhcb3 mutants: in the lhcb3 mutant used here (SALK_036200 or N536200), the protein levels of the other LHCB members were not affected (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistently, previous studies showed that down-regulation of the LHCB members reduced plant tolerance to environmental stresses with lowered seed production (Andersson et al , 2001, 2003; Ganeteg et al , 2004; Kovacs et al , 2006) except for the lhcb3 mutant that showed comparable seed production with that of wild-type plants (Damkjaer et al , 2009). The differences observed in the lhcb3 mutants between our present observations and the previously reported data (Damkjaer et al , 2009) may be due to the characteristics of the different lhcb3 mutants: in the lhcb3 mutant used here (SALK_036200 or N536200), the protein levels of the other LHCB members were not affected (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…ABA signal transduction has been extensively studied, and numerous signalling components have been identified, which include plasma membrane and intracellular ABA receptors (Shen et al , 2006; Fujii et al , 2009; Ma et al , 2009; Pandey et al , 2009; Park et al , 2009; Wu et al , 2009; Cutler et al , 2010; Shang et al , 2010). Previous reports showed that the members of the LHCB family play an important role in plant adaptation to environmental stresses (Andersson et al , 2001, 2003; Ganeteg et al , 2004; Kovacs et al , 2006), as well as their expression being regulated by ABA (Bartholomew et al , 1991; Chang and Walling, 1991; Weatherwax et al , 1996; Staneloni et al , 2008). However, it remains unknown whether the decline of plant stress tolerance due to a lack of the LHCB proteins is associated with the plant response to ABA under environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…by the extent of photosynthetic carbon assimilation, which also impacts on the reproductive fitness3435. In Arabidopsis, the leaves expand strongest between the 8-leaves-stage (stage 1.0836) and bolting (stage 536).…”
Section: Resultsmentioning
confidence: 99%
“…9A). Because the LHCB5 gene is known to be overexpressed in plants that do not express the LHCB1 and LHCB2 proteins (Ruban et al , 2003), the expression of LHCB5 was also analysed. However, the expression levels of LHCB5 were not significantly different in anu10-1 and L er (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A lower amount of LHCII trimers in anu10-1 thylakoids was detected here, in line with the proposed role of trimeric LHCII complexes in thylakoid stacking. Reduced levels of LHCII trimers in the gdc1-3 mutant have been linked to impaired grana stacking in Arabidopsis (Cui et al , 2011), and other authors have shown that normal thylakoid stacking can still occur in plants with reduced levels of LHCB1 and LHCB2 (Andersson et al , 2003), which are compensated by higher levels of LHCB5 (Ruban et al , 2003). Stacks of thylakoidal membranes have been found in other mutants with reduced levels of LHCB transcripts, such as genomes uncoupled1 ( gun1 ) (Susek et al , 1993), immutans (Wetzel et al , 1994), and CAB underexpressed4 (cue4) and cue9 (Lopez-Juez et al , 1998).…”
Section: Discussionmentioning
confidence: 99%